UNEMPLOYMENT, POVERTY, AND NATIONAL SECURITY: IMPLICATION FOR SUSTAINABLE DEMOCRACY IN NIGERIA - WANAN CORNELIUS TERZUNGWE; GABRIEL TYOYILA AKWEN; MUHAMMED SANI YUSUF; AMOS ASONGO JEV (Innovare Journal of Social Sciences, 2025)
This study examined the relationship between unemployment, poverty, and national security, anchored on a psychological, frustrated aggression theory. The research argues that unemployment is a cause of poverty and a problem for national security. This scenario puts Nigeria’s democratic survival at peril, lacking the peace and security that democracy needs to thrive. Such individuals would be poor in a country with many unemployed people because they would not be able to participate effectively in the country’s socioeconomic development, which jeopardizes lives and property through discussing the maintenance of democracy in Nigeria and extrapolated in the research. The study employed the qualitative approach using primary and secondary data drawn from online sources, journals, and newspapers. The findings indicate increasing investment in the country’s socioeconomic initiatives and programs to combat poverty and unemployment. The working-age population should be broadly reoriented toward the need for self-employment, as the government alone cannot offer the necessary jobs. The study recommends that technical education be promoted and revived as a surefire method of developing youths’ capacity for self-employment.